Activating and Increasing Employability of Specific Vulnerable Groups in Bulgaria : A Diagnostic of Institutional Capacity - World Bank (Sofia, 2015)
The Bulgarian labor market has suffered from the economic crisis, and cyclical unemployment has turned into structural unemployment. The labor market crisis is amplified by demographic change as the young and skilled labor force emigrates, aggravating a skills mismatch. Vulnerable groups are served by up to five different agencies, depending on the type of services required: the (1) public employment service; (2) social assistance agency; (3) national security institute; (4) ministry of education; and (5) national and territorial expert medical commissions. Cooperation between the labor offices, the social assistance directorates and municipalities is focused mainly on administrative functions and rule enforcement, rather than on labor market inclusion and promotion. This report reviews the design and implementation of activation policies for social assistance recipients and other highly disadvantaged groups in Bulgaria. The report starts by providing an overview of recent labor market trends, including the impact of the economic crisis on the labor market, in general, and on vulnerable groups, in particular. Chapter two describes and analyses the institutional setting for the design and implementation of Bulgaria's activation strategy and policies, as well as institutional capacity and cooperation between institutions. Chapter three analyses the impact of the benefit system on activation. Chapter four reviews the activation process and the implementation of the mutual obligation principle and the targeting of services provided to disadvantaged groups. Chapter five reviews active labor market programs and investigates to what extent these programs are targeted towards disadvantaged groups, which types of programs are prioritized, as well as reviewing the development of funding for active measures and programs.